Konstruksi Framing Ekoteologi di Media Sosial dan Implikasinya Bagi Kesadaran Ekologis Gen Z - Mustain, Mustain; Sriyanto, Agus; Ramdani, Diki (UIN Sunan Ampel Surabaya, 2026)
The global enviromental crisis calls for a new approach capable of integrating religious values with the public’a ecological awareness, particulary among Generation Z, who live in a digital ecosystem. This study aims to analyze the construction of eco-theological narratives in digital da’wah and content and to explain their implications for the formation of ecological awareness among Gen Z. This study employs a qualitative approach using a case study design. Data were collected through in-depth interviews with enviromental community leaders, non-participant observation, documentation of digital content, and a literature review. Data analyis involved idetifying essential themes that shaped the informants’ experiences, while Robert M. Entman’s framing analysis was used to examine the narrative construction in digital content and da’wah addresing enviromental issues. The results indicate that eco-theological narratives are constructed hrough the reinterpretation of Qur’anic values, particularly the concepts of fasad fil ardh, khalifah, amanah, and mizan, which are contextualized within contemporary ecological issues such as climate change, pollution, deforestation, and waste management. These narratives are presented through visual strategies, symbolism, storytelling, and persuasive communication, thereby connecting Islamic teachings with everyday ecological experiences. This study also suggests that the development of ecological awareness occurs through direct experience, spiritual reflection, digital learning, sustainable living practices, community empowerment, and setting an example through concrete actions. Although each community develops different narrative patterns, all are oriented toward fostering sustainable ecological behavior. These findings confirm that Islam functions not only as a medium for transmitting normative teachings but also as an instrument of social transformation capable of fostering ecological awareness and promoting environmental behavioral change among Generation Z.